QUALITY IN EDUCATION - Sandrock, Keith (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: This is an attempt to set out a methodology for improving quality in a university department. AFRIKAANSE OPSOMMING: Hierdie bydrae is 'n poging om 'n prosedure vir die verbetering van kwaliteit binne die departement van 'n universiteit uiteen te sit.